Effects of epigenetic pathway inhibitors on corticotroph tumour AtT20 cells. Issue 3 (March 2020) - Lines, K E; Filippakopoulos, P; Stevenson, M; Müller, S; Lockstone, H E; Wright, B; Knapp, S; Buck, D; Bountra, C; Thakker, R V
Abstract : Medical treatments for corticotrophinomas are limited, and we therefore investigated the effects of epigenetic modulators, a new class of anti-tumour drugs, on the murine adrenocorticotropic hormone (ACTH)-secreting corticotrophinoma cell line AtT20. We found that AtT20 cells express members of the bromo and extra-terminal (BET) protein family, which bind acetylated histones, and therefore, studied the anti-proliferative and pro-apoptotic effects of two BET inhibitors, referred to as (+)-JQ1 (JQ1) and PFI-1, using CellTiter Blue and Caspase Glo assays, respectively. JQ1 and PFI-1 significantly decreased proliferation by 95% ( P < 0.0005) and 43% ( P < 0.0005), respectively, but only JQ1 significantly increased apoptosis by >50-fold ( P < 0.0005), when compared to untreated control cells. The anti-proliferative effects of JQ1 and PFI-1 remained for 96 h after removal of the respective compound. JQ1, but not PFI-1, affected the cell cycle, as assessed by propidium iodide staining and flow cytometry, and resulted in a higher number of AtT20 cells in the sub G1 phase. RNA-sequence analysis, which was confirmed by qRT-PCR and Western blot analyses, revealed that JQ1 treatment significantly altered expression of genes involved in apoptosis, such as NFκB, and the somatostatin receptor 2 (SSTR2) anti-proliferative signalling pathway, including SSTR2. JQ1 treatment also significantly reduced transcription and protein expression of the ACTH precursor pro-opiomelanocortin (POMC) and ACTH secretion by AtT20 cells. Thus, JQ1 treatment has anti-proliferative and pro-apoptotic effects on AtT20 cells and reduces ACTH secretion, thereby indicating that BET inhibition may provide a novel approach for treatment of corticotrophinomas.